The creative process in the construction of a carnival costume: in search of a methodology (ModaPalavra e-periódico, 2020)
Theparade of samba schools in Rio de Janeiro is a seasonaland thematic party that is performed by several professionalslinked to the creation of services and products, depending onthe party. In this article we analyze issues in the creativeprocess of thedesigner Severo Luzardo, when designing acostume. Thus, we intend to emphasize the relations betweencarnival and design, inserting the carnival practice as a"particular form of design". For this we present a carnivalcostume inspired by corn and the consequent materializationof this project (from the sketch to the fantasy-readyprototype), weaving parallels with the methodologicalprocesses of fashion design and product design. We intend todiscover practices that reveal us design processes and thatlead us to approach the carnival to the academic practice ofdesign.
Keywords: carnival; methodology; carnival costume